Changes in Magnetic Resonance Imaging Radiomic Features in Response to Androgen Deprivation Therapy in Patients with Intermediate- and High-risk Prostate Cancer. Issue 6 (June 2022) - Tharmalingam, H.; Tsang, Y.M.; Alonzi, R.; Beasley, W.; Taylor, N.J.; McWilliam, A.; Padhani, A.; Choudhury, A.; Hoskin, P.J.
Abstract: Aims: The benefits of neoadjuvant androgen deprivation therapy (nADT) in the management of intermediate- and high-risk prostate cancer patients have been well-established. The aim of this study was to identify radiomic prognostic features derived from routine anatomic magnetic resonance imaging (MRI) sequences that can predict the response of the prostate cancer to nADT. Materials and methods: Patients with intermediate- and high-risk prostate cancer (with one of clinical stage ≥ T2c, Gleason score ≥7 or presenting prostate-specific antigen ≥10) who received 3 months of ADT prior to radical external beam radiotherapy were enrolled into this study. The relative blood volume and the relative blood flow were used as dynamic MRI kinetic parameters to quantify vascular changes as responses to nADT. For all pre- and post-nADT data sets, a combination of T2-weighted and contrast-enhanced T1-weighted anatomic images were used to define regions of interest (ROI) as the dominant malignant nodules (DMNs) and the benign prostate (the entire prostate with the summed DMNs being subtracted). MRI textural radiomic features associated with prostate cancer response in the literature of energy and homogeneity were selected. Pyradiomics was used to extract textural features of the ROIs. A Wilcoxon signed-rank test was carried out to investigate if there were statistically significant differences in values of radiomic features between: (i) benign prostate ROI and DMN pre-nADT; (ii) pre- and post-nADT of benign prostate ROI; (iii) pre- and post-nADT of DMN. Changes in radiomic features and dynamic MRI kinetic parameters were correlated using the Spearman correlation test. Results: Twenty prostate cancer patients were recruited into the study. The median time between the first baseline scan and the first on-treatment scan was 91.5 days (range 82–105). One patient had no discernible tumour visible, leaving 19 patients with evaluable data for the analysis. Baseline homogeneity and energy values differed significantly between benign and malignant tissue ( P < 0.01). In response to nADT, homogeneity and energy showed reciprocal changes, significantly increased in benign prostate while decreasing in the DMN. The reduction in tumour homogeneity and energy feature values showed a positive association with the decline in tumour blood flow and tumour blood volume induced by androgen deprivation as derived from dynamic MRI parameters. Conclusion: Energy and homogeneity radiomic features derived from MRI of benign and malignant prostate showed significant reciprocal changes in response to nADT. This study confirms the potential of these radiomic features to act as surrogate markers of tumour androgen sensitivity due to their strong association with ADT-induced physiological effects in prostate tumours. Highlights: This study identified radiomic features derived from anatomic magnetic resonance imaging that can predict the physiological response of prostate cancer to neoadjuvant androgen deprivation therapy (nADT). Baseline homogeneity and energy radiomic features differed significantly between benign and malignant tissue. In response to nADT, homogeneity and energy showed reciprocal changes, significantly increasing in benign prostate while decreasing in malignant nodules. The reduction in tumour homogeneity and energy feature values showed a positive association with the decline in tumour blood flow and blood volume induced by ADT.